Roma children’s access to education during COVID-19 pandemic: The case of Albania - Tana, Ardian; Hasa, Erjona; Shengjergji, Armando; Osmanaj, Elisabeta (Linguistics and Culture Review, 2021)
This study focuses on the education of Roma children in Albania during the pandemic conditions due to the SARS CoV-2 virus. The effectiveness of the teaching & learning process during this period has been low, especially for Roma children, who even under normal conditions result the ones lacking quality access to the education system. The study advances the hypothesis that Roma pupils are the category that did not have access during pandemics to the teaching and learning process. The purpose of the study is to highlight the situation roma children faced during the pandemic, the level & quality of the access they had to this process and to provide some recommendations for improving the situation. The research questions raised in our study, were answered through interviews conducted with Roma children’s parents and teachers at schools in Elbasan where the number of these children is high. The data and results of the study have proven the hypotheses that were advanced. The recommendations are directed tothe central governance institutions as well as tothe local government.